PENGARUH MOTIVASI DAN KEPEMIMPINAN TERHADAP DISIPLIN KERJA - RAHMAT RUDIYANTO; MEGA AYU PRAPTI NINGRUM (AKADEMIKA, 2020)
Discipline is a factor needed to improve employee performance in a company / agency. To improve discipline, it is necessary to first examine what factors influence discipline. The purpose of this study was to analyze and prove work motivation and leadership towards employee work discipline at the UPT Road, Bridge and Road Complement Maintenance (UPT Bina Marga Pagak) in Pagak District, Malang Regency. This research was conducted at the UPT Road, Bridge and Road Complement Maintenance (UPT Bina Marga Pagak) in Pagak Subdistrict, Malang Regency, by taking samples with data enhancement methods by distributing questionnaires to 40 employees. This type of research is explanatory research. The research method used is multiple linear regression test, coefficient determination test, t test and F test. The partial results of the analysis show that motivation has a positive effect on discipline and leadership which has a positive and significant effect on employee work discipline. There is a positive influence simultaneously between motivation and leadership on the work discipline of the employees of the UPT Road, Bridge and Road Complementary Maintenance (UPT Bina Marga Pagak). And it can be ignored that the variables that work motivation and employee leadership have a significant effect on employee work discipline at the UPT Road, Bridge and Road Complementary Maintenance Office (UPT Bina Marga Pagak). Based on the conditions that occur in the field, this study produces recommendations for future work improvements related to improving employee discipline, so it is important for companies to pay attention to the leadership factor of the company leadership itself. In addition, meeting the needs of employees in order to motivate employees must also pay attention to increasing employee work discipline